Multi-source uncertain entity resolution: Transforming holocaust victim reports into people. (April 2017) - Sagi, Tomer; Gal, Avigdor; Barkol, Omer; Bergman, Ruth; Avram, Alexander
Abstract: In this work we present a multi-source uncertain entity resolution model and show its implementation in a use case of Yad Vashem, the central repository of Holocaust-era information. The Yad Vashem dataset is unique with respect to classic entity resolution, by virtue of being both massively multi-source and by requiring multi-level entity resolution. With today's abundance of information sources, this project motivates the use of multi-source resolution on a big-data scale. We instantiate the proposed model using the MFIBlocks entity resolution algorithm and a machine learning approach, based upon decision trees to transform soft clusters into ranked clustering of records, representing possible entities. An extensive empirical evaluation demonstrates the unique properties of this dataset that make it a good candidate for multi-source entity resolution. We conclude with proposing avenues for future research in this realm. Abstract : Highlights: Uncertain Entity Resolution allows creating multiple narratives from complementary sources of data. The approach was demonstrated during a unique project performed on the Yad Vashem Names database . Algorithms implementing the approach were empirically evaluated on a tagged subset on various configurations and versus equivalent algorithms. The accurate and insightful results are being integrated into Yad Vashem systems and user applications.